Investigating the Activity Status of Inflammatory Bowel Disease and its Related Factors: A Study Protocol - Mehrnaz Asgharnezhad; Ehsan Amini-Salehi; Niloofar Faraji; Soheil Hassanipour; Saman Maroufizadeh; Adele Isanazar; Marjan Mahdavi-Roshan; Zahra Hedayatzadeh; Farahnaz Joukar; Fariborz Mansour Ghanaei (Caspian Journal of Health Research)
Background: While the prevalence of inflammatory bowel disease (IBD) is rising globally, there is limited knowledge regarding its activity status and associated factors, especially in Guilan Province, Iran. Objectives: This protocol outlines a case-control study aiming to assess the activity status of IBD and explore its related factors in the region. Materials & Methods: The study will utilize a case-control design of patients with IBD. Cases will consist of individuals with active IBD, while controls will be selected from those with inactive diseases. The selection of participants will be based on predefined criteria and matched for age and gender. A comprehensive set of variables will be examined, including demographic characteristics, nutritional status, lifestyle factors, medical history, and disease-related factors. Standardized questionnaires will gather information on disease activity, symptomatology, lifestyle behaviors, and nutritional status. Statistical analyses will be conducted to evaluate the association between disease activity status and the identified factors. Regression models will be employed to control for potential confounders and assess the independent effects of each variable. Conclusion: The findings from this study are expected to provide valuable insights into the activity status of IBD and its related factors in Guilan Province, Iran. By examining a range of variables, the study aims to enhance our understanding of the disease activity and identify potential modifiable risk factors. The results may have implications for improved management strategies with IBD in this region.